Psikodinamika Resiliensi Istri: Peran Determinasi Self-Love dan Coping Spiritual dalam Keharmonisan Keluarga - Fithri Choirunnisa Siregar; Mahyudin Ritonga; Desi Asmaret; Wulandari Wulandari (Attractive : Innovative Education Journal, 2026)
The resilience crisis experienced by wives within modern family structures is often rooted in a disconnection between intrapersonal needs and transcendental orientation. This study aims to provide an in-depth analysis of the psychodynamics of wives’ resilience by positioning self-love as a manifestation of hablumminannas (the horizontal dimension of human relationships) and spiritual coping as a manifestation of hablumminallah (the vertical dimension of the relationship with God) in maintaining family harmony. Employing a qualitative approach with an interpretative phenomenological design, data were collected through in-depth interviews with married women who had encountered significant family stressors yet successfully maintained domestic stability. Data were analyzed using an explicative analysis technique to uncover the essential structure of participants’ lived experiences. The findings reveal that self-love determination functions as an ego-regulating mechanism that prevents pathological self-abnegation, while spiritual coping serves as a cognitive reappraisal mechanism that transforms suffering into theological meaning. The integration of these two dimensions forms a “theo-psychological resilience axis” that enables wives to transcend primitive self-defense mechanisms and achieve mature adaptation. The originality of this study lies in its reconceptualization of self-love, which is often perceived as selfish within secular perspectives, as an ethical obligation to safeguard the trust of the self within the framework of Islamic spirituality. The findings underscore the importance of family-based clinical interventions that integrate self-esteem enhancement through self-appreciation and transcendental spiritual support.